A collocation framework to retrieve tropospheric delays from a combination of GNSS and InSAR. Issue 4 (4th November 2020) - Shehaj, Endrit; Wilgan, Karina; Frey, Othmar; Geiger, Alain
Abstract: High spatio‐temporal variability of atmospheric water vapor affects microwave signals of Global Navigation Satellite Systems (GNSS) and Interferometric Synthetic Aperture Radar (InSAR). A better knowledge of the distribution of water vapor improves both GNSS‐ and InSAR‐derived data products. In this work, we present a collocation framework to combine and retrieve zenith and (relative) slant tropospheric delays. GNSS and InSAR meteorological products are combined aiming at a better retrieval of the atmospheric water vapor. We investigate the combination approach with synthetic and real data acquired in the Alpine region of Switzerland. Based on a closed‐loop validation with simulated delays, a few mm accuracy is achieved for the GNSS‐InSAR combination in terms of retrieved ZTDs. Furthermore, when real delays are collocated, the combination results are more congruent with InSAR computed products. This research is a contribution to improve the spatio‐temporal mapping of tropospheric delays by combining GNSS‐derived and InSAR‐derived delays.